High-entropy carbonitride / oxide composite ceramic for cutter as well as preparation method and application of high-entropy carbonitride / oxide composite ceramic
The high-entropy carbon nitride/oxide composite ceramics sintered by carbon thermal reduction nitriding method are synthesized and discharged plasma sintered, which solves the problems of sintering difficulties and insufficient toughness in tool applications, and achieves high hardness, toughness and long-life cutting effects.
Patent Information
- Application Number
- CN202411954236.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-15
AI Technical Summary
The existing high-entropy carbon nitride ceramics have problems such as difficulty in sintering and poor toughness in tool applications, which are difficult to meet the high-speed and long-life cutting needs of high hardness, high cutting temperature and bonded materials.
The high-entropy carbon nitride/oxide composite powder was synthesized by carbon thermal reduction nitriding method, and the high-entropy carbon nitride/oxide composite ceramic was prepared by discharge plasma sintering technology. The specific molecular formula is (TixVyMezHfnWm)(C0.7N0.3)-(HfMe)O2. By introducing W elements and oxides, the second phase strengthening mechanism is formed to improve the hardness and toughness of the ceramic.
The high hardness and toughness of high entropy carbon nitride/oxide composite ceramics have been achieved, the cutting life of the tool has been improved to more than 1800s, and the cutting application range for high hardness, high cutting temperature and bonded materials has been expanded.
Smart Images

Figure CN119822835A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of high entropy ceramic materials, and more specifically, relates to a high entropy carbonitride / oxide composite ceramic for cutting tools, a preparation method thereof and an application thereof. Background Art
[0002] With the development of aviation, aerospace, electronics, communications and other technologies as well as machinery, chemical industry, energy and other industries, higher and more requirements are put forward for the performance of materials, and traditional single materials can no longer meet the requirements. High entropy ceramics have shown great application potential in many fields due to their unique high entropy effect, lattice distortion effect and excellent physical and chemical properties. Among them, high entropy carbonitride ceramics are high entropy materials with both multiple cations and anions. Compared with high entropy carbides and high entropy nitrides, they not only inherit many advantages of high entropy ceramics, but also further improve the mechanical properties and resistance to high temperature oxidation and ablation wear by introducing multi-element ions. However, there are some disadvantages such as difficult sintering and poor toughness.
[0003] When used as a cutting tool, it is necessary to study the problem of toughening and obtaining higher strength. In patent CN 202211151004.0, the mechanical properties of high-entropy ceramics are improved by the second phase strengthening mechanism of in-situ formation of W2C particles, and high-strength and toughness high-entropy carbonitride ceramics are obtained. However, due to the high hardness of the particles generated in situ, they will hinder cutting and cause uneven cuts, and are not suitable for cutting softer materials such as alloys. In patent CN 202211707265.6, by adding transition metals as the second phase, the good hardness and friction and wear properties of high-entropy carbonitride ceramics are maintained. Although the brittleness of ceramic materials is effectively improved, the metal may bond at high temperatures, affecting the cutting life, and the high-temperature performance is low. In patent CN 202110633888.2, Nb2O5 oxide enters high-entropy carbonitride ceramics, but eventually re-precipitates in the form of ZrO2. This process refines the oxide and can be distributed as a second phase dispersed phase in high-entropy carbonitride ceramics to play a toughening role. However, high-entropy carbonitride ceramics in which the oxide is not re-precipitated in the form of ZrO2 have low toughness, and it is necessary to find more general methods to improve the mechanical properties of high-entropy carbonitrides so as to facilitate their application in the field of tool cutting. Summary of the invention
[0004] In order to solve the above-mentioned deficiencies and shortcomings of the prior art, a high entropy carbonitride / oxide composite ceramic for cutting tools is provided. The composite ceramic has component stability and high hardness and toughness.
[0005] Another object of the present invention is to provide a method for preparing the high entropy carbonitride / oxide composite ceramic for cutting tools.
[0006] Another object of the present invention is to provide an application of the high entropy carbonitride / oxide composite ceramic for cutting tools.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] A high entropy carbonitride / oxide composite ceramic for cutting tools is prepared by first adding oxides of TiO2, V2O5, HfO2, WO3, Me and graphite powder into a solvent, ball milling to obtain a mixed powder, and then molding the obtained green body into a graphite crucible, introducing N2 throughout the process, and keeping the temperature at 1400-1600° C. to obtain a composite powder, heating the composite powder to 800-1200° C., starting to fill with a protective atmosphere and pressurizing with 10-30 MPa, and then spark plasma sintering at 1800-2000° C. to obtain the composite ceramic; the composite ceramic is (TixVyMezHfnWm)(C 0.7 N 0.3 )-(HfMe)O2, wherein 0.1≤x≤0.9, 0.1≤y≤0.9, 0.1≤z≤0.9, 0.1≤n≤0.9, 0.1≤m≤0.9, and x+y+z+n+m=1.
[0009] Preferably, the relative density of the composite ceramic is >98%, the hardness is 35-40GPa, and the fracture toughness is 10-14MPa·m 1 / 2 , the cutting life is 1800~1900s.
[0010] Preferably, the particle size of the composite powder is 0.25-0.5 μm, and the grain size of the composite ceramic is 1-1.32 μm.
[0011] Preferably, the composite ceramic (TixVyMezHfnWm) (C 0.7 N 0.3 )-(HfMe)O2 wherein Me is Zr, Nb, Ta, Cr or Mo.
[0012] Preferably, the solvent is ethanol or acetone; and the protective atmosphere is N2 or Ar.
[0013] The method for preparing the high entropy carbonitride / oxide composite ceramic for cutting tools comprises the following specific steps:
[0014] S1. TiO2, V2O5, HfO2, WO3, Me oxides and graphite powder are added to a solvent and a ball milling medium, mixed on a ball mill, and dried to obtain a mixed powder;
[0015] S2. The mixed powder was molded into a graphite crucible, N2 was introduced throughout the process, the temperature was raised to 600-800°C, and then the temperature was raised to 1400-1600°C for insulation to obtain (TixVyMezHfnWm)(C 0.7 N 0.3 )-(HfMe)O2 composite powder;
[0016] S3. The composite powder is placed in a graphite mold, heated to 800-1200°C, filled with a protective atmosphere and pressurized to 10-30 MPa, and then heated to 1800-2000°C for spark plasma sintering to obtain a high entropy carbonitride / oxide composite ceramic with a molecular formula of (TixVyMezHfnWm)(C 0.7 N 0.3 )-(HfMe)O2.
[0017] Preferably, the mixing time in step S is 12 to 24 hours.
[0018] Preferably, in step S2, the rate of heating to 600-800°C is 5-10°C / min, the rate of heating to 1400-1600°C is 2-5°C / min, and the insulation time is 1-2h.
[0019] Preferably, the heating rates to 800-1200° C. and to 1800-2000° C. in step S3 are both 50-100° C. / min; the sintering time is 5-10 min.
[0020] Application of the high entropy carbonitride / oxide composite ceramic in the cutting field.
[0021] The high entropy carbonitride / oxide composite ceramic for cutting tools of the present invention is obtained by carbon thermal reduction nitridation method using TiO2, V2O5, oxide of Me, HfO2, WO3 and graphite powder as raw materials (TixVyMezHfnWm)(C 0.7 N 0.3 )-(HfMe)O2 high entropy carbonitride / oxide composite powder is produced by spark plasma sintering. Its performance is improved and it is suitable for tool cutting applications, achieving high-speed and long-life cutting of high-hardness, high-cutting temperature, and easily bonded materials (such as gray cast iron, ductile iron, and composite materials).
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The present invention adopts a high entropy carbonitride / oxide composite powder synthesized by a carbon thermal reduction nitridation method. Under the action of carbon and nitrogen, transition metal oxides will form corresponding transition metal carbides and nitrides, and the oxygen element will eventually be removed in the form of CO or CO2. Transition metal carbides and nitrides can usually be dissolved into carbonitrides, such as Ti(C,N). Multiple transition metal carbides and nitrides will form multi-component carbonitrides during the solid solution process. As the solid solution proceeds, various solid solution reactions will occur between the transition metal carbides and nitrides produced by the above reaction, and finally a high entropy carbonitride / oxide composite powder with a small powder particle size is generated.
[0024] 2. The high-entropy carbonitride / oxide composite ceramic prepared by spark plasma sintering in the present invention has a small crystal particle size of the high-entropy ceramic powder synthesized by the carbothermal reduction nitridation method and a fast spark plasma sintering speed, thereby improving the hardness and toughness of the composite ceramic.
[0025] 3. The high entropy ceramics prepared by the present invention are difficult to completely enter the lattice structure of high entropy carbonitrides during the nitridation process due to the low chemical affinity between W and N, resulting in W enrichment at the grain boundaries and in-situ generation of particles WC and W2C. The comprehensive mechanical properties of high entropy carbonitride / oxide composite ceramics are improved through the second phase strengthening mechanism, while the hardness is retained and the toughness is improved, the cutting life of the composite ceramic tool is effectively improved, and the tool cutting life reaches more than 1800s, further expanding the scope of use of cutting materials.
[0026] 4. (TixVyMezHfnWm) (C 0.7 N 0.3 )-(HfMe)O2 high-entropy carbonitride / oxide composite ceramics achieve the in-situ generation of uniformly distributed metal oxide particles in the high-entropy phase, and improve the fracture toughness of the composite ceramics through toughening mechanisms such as crack deflection and crack bifurcation.
[0027] Description of the attached figure
[0028] Figure 1 : This is the XRD pattern of the high entropy carbonitride / oxide composite powder in Examples 1-3.
[0029] Figure 2 : XRD diagram of the high entropy carbonitride / oxide composite ceramic in Examples 1-3.
[0030] Figure 3 This is the EDS image of the high entropy carbonitride / oxide composite ceramic in Example 2-3.
[0031] Figure 4 is (Hf in Example 3 0.2 Ti0.2 V 0.2 W 0.2 Zr 0.2 )(C 0.7 N 0.3 Crack growth diagram of )-(HfZr)O2 high entropy carbonitride / oxide composite ceramics. DETAILED DESCRIPTION
[0032] The content of the present invention is further described below in conjunction with specific examples, but it should not be construed as limiting the present invention. If not specifically indicated, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0033] Example 1
[0034] 1. Add 0.2 mol HfO2, 0.2 mol TiO2, 0.2 mol WO3, 0.1 mol V2O5, 0.1 mol Nb2O5 and 3.1 mol graphite powder into ethanol, use Si3N4 balls as the ball milling medium, mix them in a ball mill, and obtain a mixed powder after drying;
[0035] 2. The green body obtained after the mixed powder molding was placed in a graphite crucible, N2 was introduced throughout the process, and the temperature was raised to 700℃ at a rate of 5℃ / min, and then raised to 1500℃ at a rate of 2℃ / min and kept at this temperature for 2h to obtain (Hf 0.2 Ti 0.2 V 0.2 W 0.2 Nb 0.2 )(C 0.7 N 0.3 )-(HfNb)O2 composite powder.
[0036] 3.(Hf 0.2 Ti 0.2 V 0.2 W 0.2 Nb 0.2 )(C 0.7 N 0.3 )-(HfNb)O2 composite powder was placed in a graphite mold and sintered by spark plasma. When the temperature was raised to 900℃ at a rate of 90℃ / min, a protective atmosphere was filled and pressure was applied. Then the temperature was raised to 1800℃ at a rate of 90℃ / min and kept for 6min. The composite ceramic of high entropy carbonitride / oxide was obtained, namely (Hf 0.2 Ti 0.2 V 0.2 W 0.2 Nb 0.2 )(C 0.7 N0.3 )-(HfNb)O2.
[0037] (Hf 0.2 Ti 0.2 V 0.2 W 0.2 Nb 0.2 )(C 0.7 N 0.3 The particle size of the composite powder of (HfNb)O2 is 0.37 μm. 0.2 Ti 0.2 V 0.2 W 0.2 Nb 0.2 )(C 0.7 N 0.3 The average particle size of the composite ceramic of )-(HfNb)O2 high entropy carbonitride / oxide is 1.17μm, the relative density is 98.3%, the hardness is 36GPa, and the fracture toughness is 11.20MPa·m 1 / 2 , the cutting life reaches 1857s.
[0038] Example 2
[0039] 1. Add 0.2 mol HfO2, 0.2 mol TiO2, 0.1 mol V2O5, 0.2 mol WO3, 0.1 mol Ta2O5 and 3.1 mol graphite powder to propanol, use Si3N4 balls as ball milling media, mix them in a ball mill, and obtain mixed powder after drying;
[0040] 2. The green body obtained after the mixed powder molding was placed in a graphite crucible, N2 was introduced throughout the process, and the temperature was raised to 700℃ at a rate of 6℃ / min, and then raised to 1500℃ at a rate of 3℃ / min and kept at this temperature for 1h to obtain (Hf 0.2 Ti 0.2 V 0.2 W 0.2 Ta 0.2 )(C 0.7 N 0.3 )-(HfTa)O2 composite powder.
[0041] 3.(Hf 0.2 Ti 0.2 V 0.2 W 0.2 Ta 0.2 )(C 0.7 N 0.3)-(HfTa)O2 composite powder was placed in a graphite mold and sintered by spark plasma. When the temperature was raised to 1100℃ at a rate of 80℃ / min, a protective atmosphere was filled and pressure was applied. Then the temperature was raised to 1900℃ at a rate of 80℃ / min and kept at that temperature for 8min. The composite ceramic of high entropy carbonitride / oxide was obtained by calcining at a pressure of 20MPa, namely (Hf 0.2 Ti 0.2 V 0.2 W 0.2 Ta 0.2 )(C 0.7 N 0.3 )-(HfTa)O2.
[0042] (Hf 0.2 Ti 0.2 V 0.2 W 0.2 Ta 0.2 )(C 0.7 N 0.3 The particle size of the )-(HfTa)O2 composite powder is 0.35 μm. 0.2 Ti 0.2 V 0.2 W 0.2 Ta 0.2 )(C 0.7 N 0.3 The average particle size of the composite ceramic of )-(HfTa)O2 high entropy carbonitride / oxide is 1.24μm, the relative density is 98.6%, the hardness is 38GPa, and the fracture toughness is 12.2MPa·m 1 / 2 , cutting life reaches 1889s.
[0043] Example 3
[0044] 1. Add 0.2molHfO2, 0.2molTiO2, 0.1molV2O5, 0.2molWO3, 0.1molZrO2 and 2.8mol graphite powder into ethanol, use Si3N4 balls as ball milling media, mix them in a ball mill, and obtain mixed powder after drying;
[0045] 2. The green body obtained after the mixed powder molding was placed in a graphite crucible, N2 was introduced throughout the process, and the temperature was raised to 800℃ at a rate of 10℃ / min, and then raised to 1600℃ at a rate of 5℃ / min and kept at this temperature for 2h to obtain (Hf 0.2 Ti 0.2 V 0.2 W 0.2 Zr 0.2 )(C 0.7 N 0.3 )-(HfZr)O2 composite powder.
[0046] 3.(Hf 0.2 Ti 0.2 V 0.2 W 0.2 Zr 0.2 )(C 0.7 N 0.3 )-(HfZr)O2 composite powder was placed in a graphite mold and sintered by spark plasma. When the temperature was raised to 1200℃ at a rate of 100℃ / min, a protective atmosphere was filled and pressure was applied. Then the temperature was raised to 2000℃ at a rate of 100℃ / min and kept at that temperature for 10min. Then the composite ceramic of high entropy carbonitride / oxide was obtained by calcining at a pressure of 30MPa. 0.2 Ti 0.2 V 0.2 W 0.2 Zr 0.2 )(C 0.7 N 0.3 )-(HfZr)O2.
[0047] (Hf 0.2 Ti 0.2 V 0.2 W 0.2 Zr 0.2 )(C 0.7 N 0.3 The particle size of the )-(HfZr)O2 composite powder is 0.25 μm. 0.2 Ti 0.2 V 0.2 W 0.2 Zr 0.2 )(C 0.7 N 0.3 The average particle size of the composite ceramic of )-(HfZr)O2 high entropy carbonitride / oxide is 1.32μm, the relative density is 99.5%, the hardness is 40GPa, and the fracture toughness is 13.28MPa·m 1 / 2 , cutting life reaches 1900s.
[0048] Figure 1 The XRD patterns of the high entropy carbonitride / oxide composite powders prepared in Examples 1-3. 0.2 Ti 0.2 V 0.2 W 0.2 Nb 0.2 )(C 0.7 N 0.3 )-(HfNb)O2 composite powder, (b) is (Hf 0.2 Ti 0.2 V 0.2 W 0.2 Ta 0.2 )(C0.7 N 0.3 )-(HfTa)O2 composite powder, (c) is (Hf 0.2 Ti 0.2 V 0.2 W 0.2 Zr 0.2 )(C 0.7 N 0.3 )-(HfZr)O2 composite powder. Figure 1 It can be seen that the composite powder has WC and W2C phases in addition to the high entropy phase. Since the crystal form of WC and W2C is a cubic structure, the solid solution rate is relatively slow and the solid solubility is relatively low. Therefore, there will be a small amount of WC and W2C phases in the composite powders of Examples 1-3, and the presence of W makes their performance better. In addition, Example 1 also contains (Hf, Nb)O2 phase impurities. Example 2 also contains (Hf, Ta)O2 phase impurities. Example 3 also contains (Hf, Zr)O2 phase impurities.
[0049] Figure 2 The XRD patterns of the high entropy carbonitride / oxide composite ceramics in Examples 1-3 are shown in Table 1. 0.2 Ti 0.2 V 0.2 W 0.2 Nb 0.2 )(C 0.7 N 0.3 )-(HfNb)O2 composite ceramic, (b) is (Hf 0.2 Ti 0.2 V 0.2 W 0.2 Ta 0.2 )(C 0.7 N 0.3 )-(HfTa)O2 composite ceramic, (c) is (Hf 0.2 Ti 0.2 V 0.2 W 0.2 Zr 0.2 )(C 0.7 N 0.3 )-(HfZr)O2 composite ceramics. Figure 2 It can be seen that except for the WC and W2C phases dissolved into the high entropy phase, the other phases have not changed and also have oxide solid solutions. Further research can be conducted on how to make the oxide solid solution evenly dispersed in it to make it have better toughness.
[0050] Figure 3 2-3 are EDS images of the high entropy carbonitride / oxide composite ceramics. 0.2 Ti0.2 V 0.2 W 0.2 Ta 0.2 )(C 0.7 N 0.3 )-(HfTa)O2 composite ceramic, (b) is (Hf 0.2 Ti 0.2 V 0.2 W 0.2 Zr 0.2 )(C 0.7 N 0.3 )-(HfZr)O2 composite ceramics. Figure 3 It can be seen that the samples are composed of high entropy phase and oxidation phase, and the uniform distribution of each metal element can be observed in the high entropy phase. Figure 3 (a)) and the aggregation of O elements, showing the (Hf,Ta)O2 phase in the sample. Hf, Zr ( Figure 3 (b)) The aggregation of O elements is shown as the (Hf,Zr)O2 phase in the sample. The formation of uniformly distributed metal oxide particles is an effective toughening mechanism, which will achieve a higher toughening effect.
[0051] Figure 4 is (Hf in Example 3 0.2 Ti 0.2 V 0.2 W 0.2 Zr 0.2 )(C 0.7 N 0.3 )-(HfZr)O2 high entropy carbonitride / oxide composite ceramics. Figure 4 It can be seen that there are more crack deflection and crack branching phenomena (white dotted circle) at the (Hf, Zr)O2 oxide in the sample. The toughening mechanisms such as crack deflection and crack branching improve the fracture toughness of the sample. 0.2 Ti 0.2 V 0.2 W 0.2 Ta 0.2 )(C 0.7 N 0.3 )-(HfTa)O2 composite ceramics have high fracture toughness. Due to their good high temperature resistance, they can be used as high temperature protection materials in extreme environments.
[0052] Example 4
[0053] 1. Add 0.1 mol HfO2, 0.1 mol TiO2, 0.2 mol V2O5, 0.3 mol WO3, 0.3 mol Cr2O3 and 2.95 mol graphite powder into ethanol, use Si3N4 balls as the ball milling medium, mix them in a ball mill, and obtain a mixed powder after drying;
[0054] 2. The green body obtained after the mixed powder molding was placed in a graphite crucible, N2 was introduced throughout the process, and the temperature was raised to 600℃ at a rate of 7℃ / min, and then raised to 1400℃ at a rate of 3℃ / min and kept at this temperature for 2h to obtain (Hf 0.1 Ti 0.1 V 0.2 W 0.3 Cr 0.3 )(C 0.7 N 0.3 )-(HfCr)O2 composite powder.
[0055] 3.(Hf 0.1 Ti 0.1 V 0.2 W 0.3 Cr 0.3 )(C 0.7 N 0.3 )-(HfCr)O2 composite powder was placed in a graphite mold and sintered by spark plasma. When the temperature was raised to 800℃ at a rate of 50℃ / min, a protective atmosphere was filled and pressure was applied. Then the temperature was raised to 1850℃ at a rate of 50℃ / min and kept at this temperature for 5min. Then, the mixture was calcined at a pressure of 10MPa to obtain (Hf 0.1 Ti 0.1 V 0.2 W 0.3 Cr 0.3 )(C 0.7 N 0.3 )-(HfCr)O2 high entropy carbonitride / oxide composite ceramics.
[0056] (Hf 0.1 Ti 0.1 V 0.2 W 0.3 Cr 0.3 )(C 0.7 N 0.3 The particle size of the )-(HfCr)O2 composite powder is 0.43 μm. 0.1 Ti 0.1 V 0.2 W 0.3 Cr 0.3 )(C 0.7 N 0.3 The average particle size of the composite ceramic of )-(HfCr)O2 high entropy carbonitride / oxide is 1.01μm, the relative density is 98.5%, the hardness is 35GPa, and the fracture toughness is 10.36MPa·m 1 / 2 , cutting life reaches 1800s.
[0057] Example 5
[0058] 1. Add 0.9 mol HfO2, 0.05 mol TiO2, 0.005 mol V2O5, 0.02 mol WO3, 0.02 mol MoO3 and 2.745 mol graphite powder to propanol, use Si3N4 balls as ball milling media, mix them in a ball mill, and obtain mixed powder after drying;
[0059] 2. The green body obtained after the mixed powder molding was placed in a graphite crucible, N2 was introduced throughout the process, and the temperature was raised to 600℃ at a rate of 8℃ / min, and then raised to 1400℃ at a rate of 4℃ / min and kept at this temperature for 1h to obtain (Hf 0.9 Ti 0.05 V 0.01 W 0.02 Mo 0.02 )(C 0.7 N 0.3 )-(HfMo)O2 composite powder.
[0060] 3.(Hf 0.9 Ti 0.05 V 0.01 W 0.02 Mo 0.02 )(C 0.7 N 0.3 )-(HfMo)O2 composite powder was placed in a graphite mold and sintered by spark plasma. When the temperature was raised to 1000℃ at a rate of 60℃ / min, a protective atmosphere was filled and pressure was applied. Then the temperature was raised to 1950℃ at a rate of 60℃ / min and kept at that temperature for 7min. Then, the mixture was calcined at a pressure of 15MPa to obtain (Hf 0.9 Ti 0.05 V 0.01 W 0.02 Mo 0.02 )(C 0.7 N 0.3 )-(HfMo)O2 high entropy carbonitride / oxide composite ceramics.
[0061] (Hf 0.9 Ti 0.05 V 0.01 W 0.02 Mo 0.02 )(C 0.7 N 0.3 )-(HfMo)O2 composite powder has a particle size of 0.5 μm. 0.9 Ti 0.05 V 0.01 W 0.02 Mo 0.02 )(C 0.7 N 0.3The average particle size of the composite ceramic of )-(HfMo)O2 high entropy carbonitride / oxide is 1.25μm, the relative density is 98.4%, the hardness is 39GPa, and the fracture toughness is 10.25MPa·m 1 / 2 , the cutting life reaches 1823s.
[0062] In summary, the particle size of the high entropy carbonitride / oxide composite ceramic composite powder measured by laser particle size analysis is 0.25-0.5 μm, the grain size of the high entropy carbonitride / oxide composite ceramic is 1-1.3 μm, the relative density is >98%, the hardness is 35-40 GPa, and the fracture toughness is 10-14 MPa·m 1 / 2 , improving the hardness and toughness of the composite ceramic. When W elements and oxides are contained, the toughness and cutting performance are improved at the same time, and the cutting life reaches more than 1800s, preferably 1800-1900s, which can further increase the cutting of high hardness, high cutting temperature, and easy-to-bond materials (such as gray cast iron, ductile iron and composite materials, etc.).
[0063] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A high entropy carbonitride / oxide composite ceramic for cutting tools, characterized in that: The composite ceramic is prepared by first adding oxides of TiO2, V2O5, HfO2, WO3, Me and graphite powder into a solvent, ball milling to obtain a mixed powder, and then molding the obtained green body into a graphite crucible, introducing N2 throughout the process, and keeping the temperature at 1400-1600° C. to obtain a composite powder, heating the composite powder to 800-1200° C., starting to fill with a protective atmosphere and pressurizing with 10-30 MPa, and then spark plasma sintering at 1800-2000° C. to obtain the composite ceramic; the composite ceramic is (TixVyMezHfnWm)(C 0.7 N 0.3 )-(HfMe)O2, wherein 0.1≤x≤0.9, 0.1≤y≤0.9, 0.1≤z≤0.9, 0.1≤n≤0.9, 0.1≤m≤0.9, and x+y+z+n+m=1.
2. The high entropy carbonitride / oxide composite ceramic for cutting tools according to claim 1, characterized in that: The relative density of the composite ceramic is >98%, the hardness is 35-40GPa, and the fracture toughness is 10-14MPa·m 1 / 2 , the cutting life is 1800~1900s.
3. The high entropy carbonitride / oxide composite ceramic for cutting tools according to claim 1, characterized in that: The particle size of the composite powder is 0.25-0.5 μm, and the grain size of the composite ceramic is 1-1.32 μm.
4. The high entropy carbonitride / oxide composite ceramic for cutting tools according to claim 1, characterized in that: The composite ceramic (TixVyMezHfnWm)(C 0.7 N 0.3 )-(HfMe)O2 wherein Me is Zr, Nb, Ta, Cr or Mo.
5. The high entropy carbonitride / oxide composite ceramic for cutting tools according to claim 1, characterized in that: The solvent is ethanol or acetone; the protective atmosphere is N2 or Ar.
6. The method for preparing a high entropy carbonitride / oxide composite ceramic for a tool according to any one of claims 1 to 5, characterized in that: The specific steps include: S1. TiO2, V2O5, HfO2, WO3, Me oxides and graphite powder are added to a solvent and a ball milling medium, mixed on a ball mill, and dried to obtain a mixed powder; S2. The mixed powder was molded into a graphite crucible, N2 was introduced throughout the process, the temperature was raised to 600-800°C, and then the temperature was raised to 1400-1600°C for insulation to obtain (TixVyMezHfnWm)(C 0.7 N 0.3 )-(HfMe)O2 composite powder; S3. The composite powder is placed in a graphite mold, heated to 800-1200°C, filled with a protective atmosphere and pressurized to 10-30 MPa, and then heated to 1800-2000°C for spark plasma sintering to obtain a high entropy carbonitride / oxide composite ceramic with a molecular formula of (TixVyMezHfnWm)(C 0.7 N 0.3 )-(HfMe)O2.
7. The method for preparing a high-performance high-entropy carbonitride / oxide composite ceramic for a tool according to claim 6, characterized in that: The mixing time in step S1 is 12 to 24 hours.
8. The method for preparing a high-performance high-entropy carbonitride / oxide composite ceramic for a tool according to claim 6, characterized in that: In step S2, the rate of heating to 600-800°C is 5-10°C / min, the rate of heating to 1400-1600°C is 2-5°C / min, and the insulation time is 1-2h.
9. The method for preparing a high-performance high-entropy carbonitride / oxide composite ceramic for a tool according to claim 6, characterized in that: In step S3, the heating rates to 800-1200° C. and to 1800-2000° C. are both 50-100° C. / min; the sintering time is 5-10 min.
10. Application of the high entropy carbonitride / oxide composite ceramic according to any one of claims 1 to 5 in the field of cutting.
Citation Information
Patent Citations
Preparation method of oxide toughened ablation-resistant high-entropy carbonitride ceramic
CN113233900A
A high-strength, high-toughness, high-entropy carbonitride ceramic and its preparation method
CN115448740B
High-entropy carbonitride / metal composite ceramic for cutter as well as preparation method and application of high-entropy carbonitride / metal composite ceramic
CN116005057A
Cited By
High-entropy carbide composite ceramic as well as preparation method and application thereof
CN121362912A